Audio-Visual Media Implementation to Improve Learning Outcomes Volleyball Service For Elementary School - Wildan; Ade Evriansyah Lubis; Karo Karo, Alan Alfiansyah Putra (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
This study aims to determine the increase in learning outcomes of volleyball underhand service through audio-visual media in fourth grade students at SD Negeri 123 Hutabargot Dolok Mandailing Natal for the 2020-2021 Academic Year. The research design used is Classroom Action Research which is intended to have an increasing impact on the object to be studied. Based on the research results that have been described, it can be concluded that there has been an increase in volleyball service learning outcomes through a reciprocal teaching style for fourth grade students at SD Negeri 123 Hutabargot Dolok Mandailing Natal for the 2020/2021 Academic Year. The results obtained from the observation were that 8 students were declared complete (44.44%) while 10 other students were declared incomplete (55.56%). In cycle I the results were obtained where 13 students were declared complete (77.23%) while the other 5 students were declared incomplete (27.77%). And in cycle II the results were obtained where 17 students were declared complete (94.44%) while 1 other student was declared incomplete (5.56%).